(untitled) (Research, Society and Development, 2020)
Milk is an essential food in human food, as it is an important source of carbohydrates, proteins, vitamins and minerals, essential nutrients for a long and healthy life. Due to the vulnerabilities, from production to shelf availability to the end consumer and as a food widely consumed by all age groups and people of all social levels, closer vigilance is required to combat tampering and abuse. product fraud. The simple practice of adding water to milk is cited as one of the most common adulterations, used to increase its volume and the producer’s profits, which is a crime and an affront to consumer rights. This paper aims to present theoretical and practical discussions, based on empirical surveys in a specialized laboratory, aimed at analyzing the quality of milk and identifying its adulteration. The work was developed at the Dairy Laboratory of the Department of Food Engineering of the Federal University of Ceará as a didactic activity in the discipline of Raw Materials of Animal Origin. The tests were performed taking samples of adulterated milk, by means of standard tests such as: Alizarol, pH, density, Dornic, among others. From the observations and analyzes made it was possible to conclude the importance of measuring the quality of milk through all the physical-chemical tests presented and to ensure a healthy product to the consumer.